CAFF Circumpolar Biodiversity Monitoring Program State of Arctic Freshwater Biodiversity Report - Conservation of Arctic Flora and Fauna (CAFF) (Arctic Council Secretariat, 2019)
Arctic freshwater ecosystems (lakes, rivers, and associated wetlands) are threatened by climate change and human development that can affect freshwater biodiversity. Such effects will change not only the distributions and abundances of aquatic species, but also the lives of Arctic Peoples that are dependent on the ecosystem services supplied by lakes and rivers. Thus, the freshwater biodiversity program of the Circumpolar Biodiversity Monitoring Program (Freshwater-CBMP) focuses on lake and river ecosystems and has established a long-term monitoring framework for these Arctic freshwaters. Developed for the Conservation of Arctic Flora and Fauna (CAFF; the biodiversity Working Group of the Arctic Council), this framework facilitates more accurate and rapid detection, communication and response to significant trends in Arctic water quality and biodiversity. Freshwater-CBMP goals are addressed in the “Arctic Freshwater Biodiversity Monitoring Plan”, which describes an integrated, ecosystem-based approach for monitoring Arctic freshwaters.